2005
DOI: 10.1007/s00439-005-0076-y
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting patterns of Y-chromosome variation in South Siberian populations from Baikal and Altai-Sayan regions

Abstract: In order to investigate the genetic history of autochthonous South Siberian populations and to estimate the contribution of distinct patrilineages to their gene pools, we have analyzed 17 Y-chromosomal binary markers (YAP, RPS4Y(711), SRY-8299, M89, M201, M52, M170, 12f2, M9, M20, 92R7, SRY-1532, DYS199, M173, M17, Tat, and LLY22 g) in a total sample of 1,358 males from 14 ethnic groups of Siberia (Altaians-Kizhi, Teleuts, Shors, Tuvinians, Todjins, Tofalars, Sojots, Khakassians, Buryats, Evenks), Central/East… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 38 publications
3
51
0
4
Order By: Relevance
“…Although we could assign haplotypes to various haplogroups, power to identify substructure within hg R1a-M198 was limited, consistent with previous work. 22,52 Although haplotype diversity is generally very high (H40.95) in all haplogroups (Supplementary Table 3), lower diversities occur in south Siberian paragroup R1a-Z93* (H ¼ 0.921), in Jewish R1a-M582 (H ¼ 0.844) and in Roma R1a-M780 (H ¼ 0.759), consistent with founder effects that are evident in the network patterns for these populations (Supplementary Figure 2).…”
Section: Y-str Haplotype Network and Diversitysupporting
confidence: 63%
“…Although we could assign haplotypes to various haplogroups, power to identify substructure within hg R1a-M198 was limited, consistent with previous work. 22,52 Although haplotype diversity is generally very high (H40.95) in all haplogroups (Supplementary Table 3), lower diversities occur in south Siberian paragroup R1a-Z93* (H ¼ 0.921), in Jewish R1a-M582 (H ¼ 0.844) and in Roma R1a-M780 (H ¼ 0.759), consistent with founder effects that are evident in the network patterns for these populations (Supplementary Figure 2).…”
Section: Y-str Haplotype Network and Diversitysupporting
confidence: 63%
“…Previous studies have shown that haplogroup R1a1-M17 is present in South Siberia from the Holocene period (11.3±3.2 Ka), 24 while the oldest age estimates dating back to Mesolithic times (approximately 18 Ka) were obtained for this haplogroup in South India and South Pakistan. 37 Similarly, high estimation of the age has been received for haplogroup R1b1b1-M73 (22.9 ± 9.3 Ka), based on variation of tri-and tetranucleotide repeats in populations of the Caucasus, South Ural and East Europe.…”
Section: Discussionmentioning
confidence: 89%
“…We reported earlier phylogeographic pattern of haplogroup R1a1-M17 in Siberian populations, indicating that Shors and Teleuts had the highest frequency of this haplogroup (more than 50%), and that R1a1-M17 generally was more frequent in populations from Altai and eastern Sayan region than in the adjacent areas. 24 Subsequent SNP analysis demonstrates that two R1b haplogroups-R1b1b1-M73 and R1b1b2-M269-are present in some Siberian populations (Table 1). R1b1b2-M269 that is frequent in Europe is rarely observed in diverse set of Siberian populations: Evenks (2.4%), Buryats (0.7%), Mongols (4.3%) and Tofalars (6.7%).…”
Section: Snp Analysis Of 885 Y Chromosomes From 16 Ethnic Groups Reprmentioning
confidence: 99%
“…17 Results of the MDS were presented by the two-dimensional plots. The genetic structure of populations was dissected by the analysis of molecular variance (AMOVA) approach, 18 22 and 236 western Eurasians belonging to J2-M172 23 were also included, in the light of the putative origins of these two haplogroups. For the integration of data between reported and present, MJ networks for R1a1-M17 haplotypes were based on seven STR loci (DYS19, DYS389I, DYS389II, DYS390, DYS391, DYS392 and DYS393), and for J2-M17 based on six STR loci (DYS19, DYS388, DYS389I, DYS390, DYS391 and DYS392).…”
Section: Discussionmentioning
confidence: 99%